The lipid peroxidation product 4-hydroxy-2-nonenal: Advances in chemistry and analysis() - Spickett, Corinne M. (Elsevier, 2013)
4-Hydroxy-2-nonenal (HNE) is one of the most studied products of phospholipid peroxidation, owing to its reactivity and cytotoxicity. It can be formed by several radical-dependent oxidative routes involving the formation of hydroperoxides, alkoxyl radicals, epoxides, and fatty acyl cross-linking reactions. Cleavage of the oxidized fatty acyl chain results in formation of HNE from the methyl end, and 9-oxo-nonanoic acid from the carboxylate or esterified end of the chain, although many other products are also possible. HNE can be metabolized in tissues by a variety of pathways, leading to detoxification and excretion. HNE-adducts to proteins have been detected in inflammatory situations such as atherosclerotic lesions using polyclonal and monoclonal antibodies, which have also been applied in ELISAs and western blotting. However, in order to identify the proteins modified and the exact sites and nature of the modifications, mass spectrometry approaches are required. Combinations of enrichment strategies with targetted mass spectrometry routines such as neutral loss scanning are now facilitating detection of HNE-modified proteins in complex biological samples. This is important for characterizing the interactions of HNE with redox sensitive cell signalling proteins and understanding how it may modulate their activities either physiologically or in disease.